Synthesis of 1,4-Disubstituted 1H-1,2,3-Triazoles from 4-(1-Adamantyl)benzyl Azide through a 1,3-Dipolar Cycloaddition Reaction - Hocine, Oussama Bencheikh le; Tebbani, Dahmane; Silva, Artur M. S. (Synlett, 2018)
A series of new 1,4-disubstituted 1H-1,2,3-triazole derivatives were synthesized by an efficient copper-catalyzed 1,3-dipolar cycloaddition reaction of 4-(1-adamantyl)benzyl azide with several terminal alkynes. The copper catalyst was used to provide 1,4-disubstituted 1,2,3-triazoles regioselectively in good yields.
Keywords: triazoles; 1,3-dipolar cycloaddition; copper catalysis; one-pot process; adamantylbenzyl azide; click chemistry